Economic analysis of sweet sorghum production systems under risk conditions - Porto, Victor Hugo da Fonseca; Cordeiro, Daltro da Silva; Kichel, Armindo Neivo; Vernetti, Isabel Helena Moreira (Pesquisa Agropecuaria Brasileira, 2014)
Since the possibility of using sweet sorghum (Sorghum bicolor Moench) for both grain and alcohol production exists, that crop might be an alternative to the monocultural trend that alcohol production imparts to some Brazilian regions. However, as sweet sorghum is recently introduced in the State of Rio Grande do Sul, it is necessary to ascertain its technical and economic viability. Thus the objective of the present study was to analyse the economic aspects of sorghum production, systems under risk conditions. The combinations of two sweet sorghum cultivars, two harvesting times, two methods of weed control and three levels of NPK (with two P sources) were analysed.